Influence of thermal annealing on structural and optical properties of Au:TiO2 nanocomposite film - Marin, A. (2013)
Two sets of nanocomposite films consisting about 4,5 at.% and 51 at.% concentrations of Au dispersed in a TiO2 dielectric matrix were deposited by DC reactive magnetron sputtering, and subjected to several thermal annealing experiments in vacuum, for temperatures ranging from 300 to 800 0C. The thermal annealing affected the size of Au nanoparticles, and also the phase of the dielectric matrix. The obtained results show that the structure and the size of Au clusters, together with the matrix crystallinity, changed as a result of the annealing, and were shown to be able to change the optical properties of the ﬁlms. The optical changes, and the correspondent Surface Plasmon Resonance effect were conﬁrmed by reﬂectivity and CIELab colour measurements. X-ray diffraction (XRD) was used to determine the thin-ﬁlm structure and crystallinity as a function of annealing temperature. The XRD data also shows clear evidence of the crystallization of the matrix in the anatase phase. With further increase of the annealing temperature, there is a change from anatase phase into rutile-type structure. Simultaneously, the Au atoms are organized in crystalline nanoparticles (revealing an fcc-type structure, with the (111) preferential growth orientation).